(untitled) (International Journal of Scientific Trends, 2023)
The primary purpose of paper is to define and study a novel type of graph function under the idea of " Gem-Set" named β^*-closed graph , ω^*-closed graph and 〖sem〗^*-closed graph , then we define K^*-map , 〖KO〗^*-map , T^*-map and T^(**)-map , then we are study the properties of it’s and the relationships with our function .